Modeling eldercare by children and children-in-law: The role of marriage institutions - Shoshana Grossbard-Shechtman (Asian Development Bank Institute (ADBI), 2017)
Informal eldercare is often supplied by family members, more so in Asia than in the West. Children and their parents as well as members of adjacent generations linked by marriage (in-laws) are modeled as self-interested agents offering or responding to material incentives. A first implication from the model is that studies of the impact of eldercare on the health and happiness of in-family caregivers could be enriched by taking account of material in-marriage transfers that the children of the needy elderly can possibly give to their spouses. A second implication discussed here is that the provision of care for older in-laws could be related to the presence of brideprice or dowry transfers (or their in-kind equivalents) and that within a society with a given set of premarital traditions the amount of such transfer will vary with the expected amount of care for elderly in-laws. Suggestive evidence was provided based on simple comparisons between some Asian and Western countries and between two Indian regions. Daughters-in-law in the rural North of India provide more eldercare than their counterparts in the South. Their families are also likely to pay lower dowries at the time of marriage, which is consistent with the model presented here. The conclusions found at the end of the paper include a list of more implications of policy relevance, especially to Asian economies.
Keywords: D1; I12; I15; I30; J12; J14; J16; D14; N15; Z13; 330; caregiving; eldercare; brideprice; dowry; marriage; in-laws; People's Republic of China; Japan; India; household finance